USE OF EPLERENONE IN PRIMARY ALDOSTERONISM DURING PREGNANCY: A CASE SERIES - Lopez, Denise Joy Emmanuelle; Rubion, Lou Erika; Maningat-Goco , Maria Patricia Deanna (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE We describe 2 patients with biochemically confirmed primary aldosteronism (PA) who were treated with eplerenone during pregnancy. Both patients were diagnosed with PA prior to pregnancy but were lost to follow-up since the pandemic. Patient 1 is a 32-year-old gravida 3 para 3 with a previous preterm delivery, seen at 26 weeks age of gestation and referred for elevated blood pressure of 160/110mmHg with severe hypokalemia. Patient 2 is a 40-year-old Gravida 6 Para 5 with previous preterm delivery as well. She was seen at 25 weeks age of gestation and referred for elevated blood pressure of 140/90mmHg and hypokalemia of 2.9 mmol/L. Both patients were given eplerenone 25 mg twice daily and had improvement in blood pressure and hypokalemia thereafter. Both patients had preterm births with birthweights appropriate for age, and APGAR scores of 9 after 5 minutes. This case series can support the efficacy of the short-term use of eplerenone to control hypertension and hypokalemia in PA during pregnancy